The Linguistic and Semantic Coherence of Surah Al-Fatihah - Mohamed Ibrahim Hassan Othman; Ibrahim Youssef Abdelhamid; Mohamad Zhafri Mohammad Nazmi; UmmuHani Binti Abas (Human Resource Management Academic Research Society, 2024)
Vol. 13, No. 6, 2023, Pg. 480 – 488